2014
DOI: 10.1073/pnas.1402785111
|View full text |Cite
|
Sign up to set email alerts
|

Compressive mapping of number to space reflects dynamic encoding mechanisms, not static logarithmic transform

Abstract: The mapping of number onto space is fundamental to measurement and mathematics. However, the mapping of young children, unschooled adults, and adults under attentional load shows strong compressive nonlinearities, thought to reflect intrinsic logarithmic encoding mechanisms, which are later "linearized" by education. Here we advance and test an alternative explanation: that the nonlinearity results from adaptive mechanisms incorporating the statistics of recent stimuli. This theory predicts that the response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
329
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(377 citation statements)
references
References 45 publications
(54 reference statements)
30
329
2
2
Order By: Relevance
“…al, (2012; see also Cicchini, Anobile, & Burr, 2014). The log-linear function has two free parameters: (i) p(log) which identifies the proportion of log fit (vs. linear fit) and, (ii) a a scaling parameter.…”
Section: Resultsmentioning
confidence: 99%
“…al, (2012; see also Cicchini, Anobile, & Burr, 2014). The log-linear function has two free parameters: (i) p(log) which identifies the proportion of log fit (vs. linear fit) and, (ii) a a scaling parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Participants then saw a test screen containing a random adjustment face, which they modified by scrolling through the continuous expression wheel to match the target expression. After picking a match expression, participants saw a 1000-ms noise mask followed by a 1000-ms fixation cross before the next trial began Cicchini et al, 2014;Cicchini, Mikellidou, & Burr, 2017;Corbett et al, 2011;Liberman et al, 2014;Manassi et al, 2017). In Experiment 3, serial dependence was not ethnicity selective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the perception of orientation, numerosity, and other low-level stimulus features is serially dependent-systematically biased (i.e., pulled) towards similar visual input from the recent past (Cicchini, Anobile, & Burr, 2014;Corbett, Fischer, &Taubert, Alais, & Burr, 2016;Xia, Leib, & Whitney, 2016), as well as in feature space (object similarity; Fritsche, Mostert, & de Lange, 2017;Liberman, Fischer, & Whitney, 2014;Manassi, Liberman, Chaney, & Whitney, 2017). The spatio-temporal region over which current object features, such as orientation, are pulled by previously seen features is known as the Continuity Field (CF).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the mental number line reported that logarithmic compression can be explained by adaptive decision-making (Cicchini et al, 2014). Cicchini et al showed that each subject's spatial response during a number line task is predicted by that subject's previous exposures to numerical values, and greater logarithmic scaling (as opposed to linear scaling) is observed under high cognitive load than low cognitive load.…”
Section: Response Competition Viewmentioning
confidence: 99%
“…Number representations are organized along a mental number line wherein small and large numbers are placed to the left and right side of space, respectively (Dehaene, Bossini, & Giraux, 1993;de Hevia & Spelke, 2009;Rugani, Vallortigara, Priftis, & Regolin, 2015; but see Núñez & Fias, 2015). Numerical positions in the spatial representation conform to a logarithmic scale: as numbers get larger their distances in the mental line get compressed (Dehaene, Izard, Spelke, & Pica, 2008;Nieder & Dehaene, 2009; but see Cantlon, Cordes, Libertus, & Brannon, 2009;Cicchini, Anobile, & Burr, 2014). Under this hypothesis, the mental number line, its left-to-right organization, and logarithmic scale directly maps to the spatial positions of reach trajectories -and some data support this hypothesis (Dotan & Dehaene, 2013;Song & Nakayama, 2008).…”
mentioning
confidence: 99%